Workplace Integration of Global Talents in the Finnish Technology Industry : An Exploration of Employee Perspective - Wickrama Arachchi Kamkanamge, Amitha (My University, 2025)
The need for global talent in the Finnish technology industry is rising due to shrinking birth rates, an ageing population, and a shortage of skilled labour. Despite the growing research focus on Global Talents, exploring their experiences from their perspective is emphasised. This study explores the contributing factors to workplace integration as perceived by global talents and the different workplace integration practices they experienced. This study achieved these twin objectives through an exploratory qualitative study, which was carried out by interviewing seven South Asian global talents in the Finnish Technology Industry. The research produced several key findings; qualitative interview data explored more meaningful factors enhancing and hindering workplace integration as perceived by global talents, while personal factors act as moderators in the workplace integration process. A set of novel and modified self-help practices and company-initiated practices were discovered, and self-help practices were driven mainly by the personal factors of global talents. The main conclusion drawn from these findings was the combined dual approach of different self-help practices and company-initiated practices strengthened workplace integration while mitigating negative effects. Personal factors played a critical role in the workplace integration process as a moderator variable and an influencing factor in deciding and executing different self-help practices. This research presents an integrated framework overarching global talents' perspectives and experiences on workplace integration. The Finnish technology industry, global talents and policymakers can enhance workplace integration by utilising these new practices and workplace contributing factors. At the same time, future researchers can expand the study to multiple other Finnish industries, expand the geographical coverage of the sample and consider a specific scale of firms to develop more specific findings.
Keywords: Workplace Integration, Global Talents, Finnish Technology Industry, Company-initiated Practices, Self-help Practices